Aplikasi Himpunan Julia dalam Membuat Rancangan Motif Fraktal Songket Palembang - Eka Susanti (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2016)
Songket is one of the Indonesian arts and culture into community characteristics Palembang. Palembang songket motifs influenced by Islamic culture, in general, Palembang songket motifs shaped flowers. In this paper are given motif fractal Palembang songket motifs Sadum Tumpal Ulos. This motif is formed from the set of Julia with , with z = a + ib and n = 5.5; n = 6 and n = z.